Ukrainian paediatrics of the future: current problems and prospects for improvement - Titkova, Olena (Futurity Medicine, 2023)
This article focuses on “Ukrainian paediatrics of the future: current problems and prospects for improvement. Aims: objectives of the research study are to identify the current problems and challenges facing paediatric healthcare in Ukraine, including issues related to healthcare professionals, infrastructure, vaccination coverage, healthcare spending and public awareness of paediatric health and prevention; areas for improvement after analyses of previous initiatives; potential for future improvements in paediatric healthcare in Ukraine, including prospects related to national vaccination programs, telemedicine and digital health, medical research, the patient-centered care, medical education and training, improved healthcare infrastructure, and public-private partnerships. Study design: Descriptive cross-sectional study Place and Duration of Study: The majority of the studies were conducted on patients, professionals’ healthcare establishment and policy maker stakeholders in the Ukraine. Methodology: In order to collect secondary data a questionnaire was used. Results: Ukraine has just 665 hospital beds per 100,000 residents in 2019 compared to 417 doctors per 100,000 in 2000. The pace of replacement for most medical equipment is sluggish. Since 2019, the rates of infant, under-five, and neonatal death have been mostly steady. The rates of BCG and measles vaccination coverage have fluctuated, although they have typically gone down. The biggest problem with paediatric healthcare in Ukraine is a lack of money, which leads to a dearth of medical personnel, supplies, and equipment, as well as a high incidence of diseases that may be prevented because of a lack of public awareness of paediatric health. Conclusion: Paediatrics faces challenges, including inadequate healthcare infrastructure and a high infant and child mortality rate. Prospects for improvement, such as the development of telemedicine and e-health services, improving maternal and child healthcare services, and increasing investment in research and development. By addressing these challenges and investing in these prospects, the country can significantly improve the health and wellbeing of its children.